1998
DOI: 10.1002/(sici)1096-8628(19980616)78:1<44::aid-ajmg9>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

De novo apparently balanced complex chromosome rearrangement (CCR) involving chromosomes 4, 18, and 21 in a girl with mental retardation: Report and review

Abstract: We describe a complex and unique, de novo apparently balanced translocation involving chromosomes 4, 18, and 21 with 4 breakpoints, in a patient who was referred for an evaluation of possible fragile-X syndrome. Fluorescence in situ hybridization (FISH) confirmed the complexity of the rearrangement and showed the derivative 21 to be composed of 3 distinct segments derived from chromosomes 21, 18, and 4. The derivative chromosome 18 had undergone a double translocation, the first such event to be described in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 88 publications
3
34
1
Order By: Relevance
“…Despite the importance of refining the multiple rearrangement breakpoints at the sequence level in CCR cases, virtually no breakpoints have been sequenced and no molecular mechanisms have been proposed for how they might occur. To date, most of the breakpoints have been mapped using conventional cytogenetic G-banded karyo-typing, multi-subtelomeric fluorescence in situ hybridization (FISH), whole chromosome painting FISH, M-FISH or SKY or multicolor banding (MCB) [34,35,4446]. …”
Section: Complexity Is Not Uncommon For Human Genome Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of refining the multiple rearrangement breakpoints at the sequence level in CCR cases, virtually no breakpoints have been sequenced and no molecular mechanisms have been proposed for how they might occur. To date, most of the breakpoints have been mapped using conventional cytogenetic G-banded karyo-typing, multi-subtelomeric fluorescence in situ hybridization (FISH), whole chromosome painting FISH, M-FISH or SKY or multicolor banding (MCB) [34,35,4446]. …”
Section: Complexity Is Not Uncommon For Human Genome Rearrangementsmentioning
confidence: 99%
“…Vissers et al [47] reported two patients in which 17 total breaks were found scattered throughout chromosomes 17 and 21; four of them mapped within low copy repeats (LCRs) usually associated with different recurrent chromosome aberrations, including those causing CMT1A, HNPP, Smith–Magenis syndrome (SMS; MIM 182290) and Potocki–Lupski syndrome (PTLS; MIM 610883). Batanian and Eswara [34] reviewed 100 CCR cases and noted that band 18q21 has an assigned breakpoint in 11/14 cases where the chromosome 18 was involved. Giardino et al [51] detected the preferential involvement of chromosomes 3, 4, 6 and 10 in 20 prenatally ascertained CCRs; particularly, they reported a patient in which the breakpoints observed on chromosomes 4 and 10 were coincident with bands containing members of the olfactory receptor family.…”
Section: Complexity Is Not Uncommon For Human Genome Rearrangementsmentioning
confidence: 99%
“…These are rare, although clinically important to recognize, because carriers can have phenotypes spanning from normal individuals, infertile males, mental retardation, to congenital abnormalities and they can be responsible for recurrent miscarriages in females [5-7]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the 7q21, 8q21, and 11p14 regions, which are involved in our patient's CCR, seem to be prone to chromosome breakage. In a recent survey of 100 CCRs, nine breakpoints were found in 18q21; seven each in 3q13 and 7q22; six in 5p13, 7q11, and 8q22; five in 1p22, 1q42, 3p13, 7q21, 9p24, 11q14, and 21q21; four in 1p13, 2q13, 2q21, 2q33, 3p11, 3q26, 7q31, 8p23, 8q13, 8q24, 11p15, 13q32, 21q11, and 21q22; and three in 1q21, 1q32, 2q22, 2q23, 3p23, 5p14, 5q15, 6p21, 6q27, 7p14, 7q36, 8q21, 9q22, 9q32, 10p12, 10q11, 10q22, 11p14, 11p13, 11q13, 11q21, 12p13, 12q22, 12q24, 13q14, 15q22, and 21p11 8. This breakpoint clustering is probably not the result of ascertainment bias, but suggests the existence of chromosomal “hot spots” involved in complex rearrangements.…”
mentioning
confidence: 99%